PENETAPAN KADAR FENOLIK TOTAL DARI EKSTRAK ETANOL BUNGA ROSELLA (Hibiscus sabdariffa L.) BERWARNA UNGU MENGGUNAKAN SPEKTROFOTOMETRI UV-VIS - Andi Herlinda; Abd. Malik; Ahmad Najib (Jurnal Fitofarmaka Indonesia, 2016)
One of the herb plants, purple Roselle flowers (Hibiscus sabdariffa L), used to traditionally for various diseases. The aim of this research is to determine the total phenolic content of ethanol extract of purple Roselle flowers. Sample as many one kilograms extracted by maceration method using ethanol 96%. Resulty 120 grams thick extract. Total phenolic content determined by UV-Vis spectrophotometer at wave leght 743 nm with gallic acid as standard reference with Folin-Ciocalteau reagent. The result show the rendamen of ethanolic extract 12% with total phenolic content 1.6726 %.